Monetary and fiscal factors in nominal interest rate variations in Sri Lanka under a deregulated regime - Biswajit Maitra (Financial Innovation, 2017)
Background: This paper examines the role of monetary and fiscal factors in interest rate variations in Sri Lanka under its deregulated regime of interest rates. In addition the paper also examines the role of monetary factors in the variation of interest rates, using a quarterly dataset for the post-global recession period, when the exchange rate is determined by market forces. Results: Empirical analysis uses a dataset of nominal interest rates, money growth, income growth, changes in nominal exchange rate, and budget deficit. From the methodological point of view the paper involves vector autoregression model and Wald tests of Granger causality, followed by impulse response analysis while stationarity and the order of integration of the selected variables are confirmed involving the augmented Dickey-Fuller and the Phillips-Perron unit-root tests. Results: The paper confirms that both monetary and fiscal factors have significant effects on the variations of interest rates. Money growth triggers an increase in interest rates, which supports the Fisher equation view, while income growth has a negative impact. Budget deficit causes a rise in interest rates, but the role of the exchange rate is found to be almost insignificant, probably due to including exchange rate series that cover both the pegged and market-based regimes of exchange rates. The second part of the analysis, using a quarterly dataset for the post-global recession period, further establishes the positive impact of M2 money growth and income growth on interest rates. In this case, exchange rate depreciation causes an increase in interest rates. Conclusions: The significant role of monetary and fiscal factors in interest rate variations implies it would be possible to manage interest rates through a judiciary management of monetary and fiscal policies.
Keywords: E43; E12; 650; Nominal interest rate; Money growth; Income growth; Exchange rate; Budget deficit; Vector autoregression